Geologia e metalogênese do depósito aurífero Ouro Roxo, Província Tapajós, Jacareacanga-PA. - VELOSO, Ângela Suélem Rocha (Universidade Federal do Pará, 2019)
The OuroRoxo gold deposit is located near São José Village at Pacuriver margin, far around 36 km from Jacareacanga city, western Tapajós Gold Province, SW portion of Para State. The OuroRoxo deposit comprises a hydrothermal system of sulfide quartz veins hosted by mylonitegranitoidTropas Intrusive Suitof Paleoproterozoic age. The ore bodies are controlled by a N-S trending shearing known as OuroRoxo-CantaGalo shear zone. The host granitoids are oxidized calc-alkaline granodiorite and tonalite with magnetite and sphene, characterized as magmatic arc granitoids.The OuroRoxoCantaGalo shear zone is a sinistral oblique ductile-brittle shear of low to middle angle which has turned the granitoids into protomylonites and mylonitesinterlayed with breccias zones. The protomylonites are characterized by predominance of porfiroclasts over the matrix composed by phengite, chlorite and quartz which grade into mylonites and minor ultramylonits with almost 100% of matrix. The mylonitic foliation is defined by chlorite, biotite and phengite along NNE-SSW direction dipping to ESE. Stretched quartz grains define a lineation which indicates the oblique tectonic movement to NNW. Shear features such as mica-fish,shadow pressure, tail recristalization and microboudinage are ubiquitous in theses rocks and indicate a sinistral kinematics for shearing. The ore bodies are quartz veins and pipes hosted by mylonites and breccias, surrounded by prominent alteration halos and concordant to mylonitic foliation. Besides silicification and sulfidation more concentrated in the ore bodies, three types of hydrothermal wall-rock alteration were recognized in alteration halos: 1) propilitic alteration: chlorite+phengite+carbonate. Four chlorite generations were identified, the last one being veinlets; 2) phylic alteration: phengite+quartz+carbonate+pyrite, with three phengite generations; 3) carbonatization with three generations of carbonate, the last one beingveinlets. Besides magmatic quartz and microcrystalline quartz of mylonites, five generations of hydrothermal quartz were recognized in the lodes, the last one beingveinlets.The ore shoots are mainly made up by pyrite and chalcopyrite, with minor bismutinite, native bismuth and gold. Besides the pyrite associated to gold and an earlier pyrite magmatic generation, late pyrite veinlets occur. Two generations of chalcopyrite were identified and the second one substitutes the pyrite 2 associated to ore. The main gange minerals are quartz, chlorite, phengite and carbonate. Azurite, bornite and covellite are copper supergenic minerals derived from alteration of chalcopyrite.Three kinds of fluids were identified in vein quartz of the OuroRoxo deposit: 1) low-to-middle salinity aqueous fluid within the H2O-NaCl-MgCl2-FeCl2systemwhich occurs in quartz 3, with Th=180-280°C; 2) brines within the H2O-NaCl-CaCl2 system which occur in quartz 4 and 6, with Th=270-400°C, and underwent dilution brought about by mixing with meteoric water, lowering its salinity and temperature (Th=120-380); 3) middle-salinity aquocarbonic fluid which occurs in quartz 3 and 4, with Th=230-430°C. The aquocarbonic fluid was interpreted as ore fluid related to shear zone with higher Th in ductile conditions. The brines origin was related to a magmatic event coeval to shearing, with lower Th in the end of the residual magmatic process.The temperature and pressure conditions of OuroRoxo deposit formation were estimated using the hydrothermal chlorite geothermometer and the isochors calculated from the fluid inclusion microthermometric data. Values range from 315 to 390°C and 2,0 to 4,2 k b. Two mechanisms were regarded to be the main cause for gold deposition. 1) Fluid- rock interaction brought about increasing of fO2 and reduction of fS2 during hydrolysis (propylitic and phylic alteration) and sulfidation reactions; 2) Mixing between aquocarbonic fluid and magmatic brines induced an increasing of fO2anddecreasing of pH. These two mechanisms would favor gold deposition in transtension sites of the shear zone.The age of ore formation, obtained by Pb-Pb method in pyrite, was estimated around 1858±130Ma. The large error of that age turn it as reference age only which shows a time relationship between the mineralization, the shearing and the Maloquinha granite event. The orogenic magmatic arc environment, the veining style, the structural control by the shear zone, the hydrothermal alteration (propylitic+philic+carbonatization), the metallic association (Au+Cu+Bi), the middle-salinity aquocarbonic ore fluid and the participation of magmatic brines in ore deposition, are all consistent to a hybrid model (orogenic with magmatic participation) for the genisis of the OuroRoxo gold deposit.